The Probiotic Lactobacillus paracasei Ameliorates Diarrhea Cause by Escherichia coli O8via Gut Microbiota Modulation1 - Ren, Shunan; Wang, Chunjie; Chen, Aorigele; Lv, Wenting; Gao, Ruijuan (Frontiers in Nutrition, 2022)
Introduction Koumiss is a fermented horse milk food containing abundant probiotics. Lactobacillus paracasei is a bacterial strain isolated from koumiss that helps regulate the intestinal microbiota. One of the major cause of diarrhea is an imbalance of the intestinal flora. The aim of this study was to investigate whether Lactobacillus paracasei can ameliorate E. coli-induced diarrhea and modulate the gut microbiota. Methods Mouse models of diarrhea were established via intragastric E. coli O8 administration. We then attempted to prevent or treat diarrhea in the mice via intragastric administration of a 3 × 108 CFU/mL L. paracasei cell suspension. The severity of diarrhea was evaluated based on the body weight, diarrhea rate, and index, fecal diameter, ileum injury, hematoxylin-eosin (H&E) staining, and diamine oxidase (DAO) and zonulin expression. Expression of the tight junction (TJ) proteins claudin-1, occludin, and zona occludens (ZO-)1 were detected by immunohistochemistry (IHC). Gastrointestinal mRNA expression levels of interleukin (IL)-6, IL-1β, and tumor necrosis factor (TNF)-α were detected by real-time polymerase chain reaction (RT-PCR). The microbial composition was analyzed by 16s rRNA sequencing. Results The L. paracasei demonstrated excellent therapeutic efficacy against diarrhea. It elevated the TJ protein levels and downregulated proinflammatory cytokines IL-6, IL-1β, TNF-α, and p65, myosin light chain 2 (MLC2), myosin light chain kinase (MLCK). Moreover L. paracasei increased those bacteria, which can product short-chain fatty acid (SCFA) such Alistipes, Odoribacter, Roseburia, and Oscillibacter. Conclusion L. paracasei ameliorated diarrhea by inhibiting activation of the nuclear factor kappa B (NF-κB)-MLCK pathway and increasing the abundance of gut microbiota that produce SCFA.